KAJIAN KARAKTERISTIK, PERSEBARAN DAN KEBIJAKAN REOG PONOROGO DI KABUPATEN PONOROGO PROVINSI JAWA TIMUR - , AJI AKBAR TITIMANGSA, Drs. Joko Christanto, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is a country with a rich culture. For example in the southeast area of East Java province there is Reog Ponorogo. In the last several years, Reog receives a lot of attention due to copyright issue. Uniqueness and development of Reog in its place of origin, Ponorogo Regency, is interesting to study. The aims of this study were (1) to discover the characteristics of Reog in Ponorogo regency, (2) to discover the distribution of Reog in Ponorogo regency area, (3) to discover the policy of Ponorogo Regency government, especially Department of Tourism, to preserve Reog in Ponorogo Regency. This study used descriptive method with qualitative approach. Sample collection method was purposive sampling method. The variables used were performance elements, types of story of Reog performance in Ponorogo Regency, number and locations of Reog studios, regional revenue, education, and financial structure. Data was collected using survey and in depth interview techniques, using checklist and documentation equipments as research instruments. Data was focused on searching keyperson who understands the history and development of Reog. The results of this study showed that: (1) Reog has ballet characteristics such as jathil, warok, gemblakan, barongan, caplokan, strong plotline with local culture. There is a transformation of the Reog definition and function, from the traditional ceremony to the show industries. Therefore, survival units is they get more opportunities to show. (2) The local distribution of the progress is related with location accessibility to the central of development district (city). Which is related with the show intesity that held at the central district. Distribution of Reog at the out of Ponorogo regency is to Deli Serdang, Salatiga, Yogyakarta, Bandung, even to abroad, Malaysia, USA, Rusia, Germany, and Netherland. Occur the aculturation with local art and tradition there. (3) The policy suggested is to keep giving supports to the development in the forms of financial aids, training, Reog competitions, establishing museum and inserting Reog into school curriculums.